Why issue green bonds? Examining their dual impact on environmental protection and economic benefits - Di Zhou; Alexios Kythreotis (Humanities & Social Sciences Communications)
Abstract This article explores two primary questions: first, whether the issuance of green bonds contributes to environmental protection, particularly regarding their performance after the adoption of net-zero emission policies; and second, whether issuers of green bonds can have economic benefits. Using the Difference-in-Differences (DID) model to analyze green and conventional bonds issued from 2013 to 2023, the study finds no significant correlation between green bond issuance and CO2 emissions following net-zero adoption. Nevertheless, our findings are important and deserve attention as they indicate that the carbon reduction policies have not exerted sufficient pressure on bond issuers to reduce emissions. At the same time, however, a closer examination of issuing entities reveals that those issuing only green bonds tend to have higher ESG ratings, lower CO2 emissions, and lower financing costs. This suggests that such issuers achieve substantial environmental benefits and economic advantages. In contrast, entities issuing both conventional and green bonds do not demonstrate the same environmental benefits. This finding raises concerns about potential greenwashing, suggesting that entities issuing both green and conventional bonds may engage in practices that contradict environmental protection while presenting their activities as environmentally friendly through green bonds. The study also highlights that the impact of bond features on ESG scores and CO2 emissions varies significantly across different types of issuers. Finally, the paper recommends that policymakers strengthen carbon reduction policies, establish mechanisms to prevent greenwashing, and integrate CO2 emissions and ESG factors into assessment systems. Additionally, it calls for special attention to the carbon emissions of entities in low- and middle-income countries, as well as those in the manufacturing sector, to support the healthy development of green finance.